Non-local integral-type damage combined to mean-field homogenization methods for composites and its parallel implementation - Lenz, Peter; Mahnken, Rolf (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Development of a rivet geometry for solid self-piercing riveting of thermally loaded CFRP-metal joints in automotive construction - Vorderbrüggen, Julian; Köhler, Daniel; Grüber, Bernd; Troschitz, Juliane; Gude, Maik; Meschut, Gerson (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Multiscale analysis of composite structures with goal-oriented mesh adaptivity and reduced order homogenization - Ju, Xiaozhe; Mahnken, Rolf; Xu, Yangjian; Liang, Lihua; Cheng, Chun; Zhou, Wangmin (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Characterization of residual stresses in fiber metal laminate interfaces - A combined approach applying hole-drilling method and energy-dispersive X-ray diffraction - Wu, T.; Degener, S.; Tinkloh, Steffen Rainer; Liehr, A.; Zinn, W.; Nobre, J.P.; Tröster, Thomas; Niendorf, T. (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

Influence of laser-generated surface micro-structuring on the intrinsically bonded hybrid system CFRP-EN AW 6082-T6 on its corrosion properties - Delp, Alexander; Freund, Jonathan; Wu, Shuang; Scholz, Ronja; Löbbecke, Miriam; Haubrich, Jan; Tröster, Thomas; Walther, Frank (Composite Structures)
Keywords: Civil and Structural Engineering; Ceramics and Composites

A micromechanical-based finite element simulation of process-induced residual stresses in metal-CFRP-hybrid structures - Tinkloh, Steffen Rainer; Wu, Tao; Tröster, Thomas; Niendorf, Thomas (Composite Structures)

Deep drawing of fiber metal laminates for automotive lightweight structures - Heggemann, Thomas; Homberg, Werner (Composite Structures)
Current challenges in the automotive industry are the reduction of fuel consumption and the CO2 emissions of future car generations. These aims can be achieved by reducing the weight of the car, which further improves the driving dynamics. In most currently mass-produced cars, the body accounts for one of the largest parts by weight, and hence designing a lightweight car body assumes great importance for reducing fuel consumption and CO2 emissions. Extremely lightweight designs can be achieved by using purely composite materials, which are very light but also highly cost intensive and not yet suitable for large scale production due to the necessity of manual processing. A promising approach for the automated, large-scale production of lightweight car structures with a high stiffness to weight ratio is the combination of high strength steel alloys and CFRP prepregs in a special hybrid material/fiber metal laminate (FML) – which can be further processed by forming technologies such as deep drawing. In current research work at the Chair of Forming and Machining Technology (LUF) at the University of Paderborn, innovative manufacturing processes are being developed for the production of high strength automotive structural components made of fiber metal laminates. This paper presents the results of technological and numerical research that is currently being performed at the LUF into the forming of hybrid fiber metal laminates. This paper focuses on the results of basic research and the individual measures (tool, process and material design) necessary for achieving the desired part quality.

Investigations on a material-specific joining technology for CFRP hybrid joints along the automotive process chain - Vorderbrüggen, Julian; Meschut, Gerson (Composite Structures)

Experimental and numerical crushing analysis of circular CFRP tubes under axial impact loading - Reuter, Corin; Sauerland, Kim-Henning; Tröster, Thomas (Composite Structures)

A mesoscopic model for deep drawing of carbon fibre prepregs at large strains - Hankeln, Frederik; Mahnken, R. (Composite Structures)